Exploring changes in injury and illness incidence and burden in elite junior male Australian footballers over a 6-year period - McDonald, J.; Bennett, H.; Fuller, J.; Jones, S.; Debenedictis, T.; Chalmers, S. (Journal of Science and Medicine in Sport, 2024)
Objectives The study aimed to determine a contemporary multi-year junior AF injury and illness profile and secondly, explore changes in incidence and burden over the six-year period.